Does voluntary social cooperation promote liberal egalitarian justice? - Hedvig Mendonca; Lida Kuang; Simon März; Larissa Walter (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2024)
The following paper emerged from the interactive sessions and lectures of the second part of the Summer School, with the topic "Social Contract Lab Experiments". It took place from June 11 to June 14, 2023 and was conducted in collaboration with Prof. Bernhard Neumärker, the FRIBIS SoCoBis Team, the leader of the SoCoLab in Freiburg, Dr. Marcel Franke and Prof. Lorenzo Sacconi, Prof. Marco Faillo, Laura Marcon (PhD.) and Dr. Viginia Cecchini Manara from Italy. The policy paper is a draft of an adapted social contracting experiment that can be seen following the various lectures and workshops, in particular the presentations by Prof. Lorenzo Sacconi, Prof. Virginia Cecchini Manara, Prof. Marco Faillo, and Laura Marcon (PhD.).
Keywords: 330